RESEARCH AND DEVELOPMENT FOR CASSAVA BASED INDUSTRY - Tajuddin Bantacut (Jurnal Teknologi Industri Pertanian, 2009)
Cassava, locally known as ubi kayu, singkong or ketela pohon, has huge potency due to: (i) can be grown in almost all climate conditions, (ii) drough resistence, (iii) raw material for many uses vary from food, feed to energy, and (iv) technically well known by community. However, there is no strong cassava based processing industry (tapioca, cassava flour, glucose syrup, and ethanol) grow with good business insight. This review sees the gap comprehensively between the capacity to produce and availability of raw material (fresh cassava), and high potency of uses and increasingly down stream product demand. This paper ends with recommendations on how to bridge upstream potency and down stream demand through the development of cassava based industry. Special discussion on Cassava Research Center is provided. Keywords:   Cassava Research Center, development, food security, biofuel